Impact Characteristics and Fatigue Life Analysis of Multi-Wire Recoil Spring for Guns - Zhifang Wei; Xiaolian Zhang; Yecang Hu; Yangyang Cheng (Shock and Vibration)
Recoil spring is a key part in automatic or semi-automatic weapons re-entry mechanism. Because the stranded wire helical spring (SWHS) has longer fatigue life than an ordinary single-wire cylindrically helical spring, it is often used as a recoil spring in various weapons. Due to the lack of in-depth research on the dynamic characteristics of the current multi-wire recoil spring in recoil and re-entry processes, the fatigue life analysis of the current multi-wire recoil spring usually only considers uniform loading and does not consider dynamic impact loads, which cannot meet modern design requirements. Therefore, this paper proposes a research method for fatigue life prediction analysis of multi-wire recoil spring. Firstly, based on the secondary development of UG, a three-wire recoil spring parameterized model for a gun is established. Secondly, ABAQUS is used to carry out a finite element analysis of its dynamic response characteristics under impact, and experimental verification is performed. Then, based on the stress-time history curve of the dangerous position obtained by finite element analysis, the rain flow counting method is used to obtain the fatigue stress spectrum of recoil spring. Finally, according to the Miner fatigue cumulative damage theory, the fatigue life prediction of the recoil spring based on the S-N curve of the material is compared with experimental results. The research results show that the recoil spring has obvious transient characteristics during the impact of the bolt carrier. The impact velocity is far greater than the propagation speed of the stress wave in the recoil spring, which easily causes the spring coils to squeeze each other. The maximum stress occurs at the fixed end of the spring. And the mean fatigue curve (50% survival rate) is used to predict the life of the recoil spring. The calculation result is 8.6% different from the experiment value, which proves that the method has certain reliability.